Tren Gaya Hidup Milenial, Identitas Sosial dan Desain Coffe Shop - Petty Arisanti (Universitas Pendidikan Nasional, 2021)
This study aims to describe the background and describe the meaning of cafes as a marker of social class identity, for young people in the city of Kediri. This research is expected to contribute to the development of insight, especially insight into the phenomenon of human behavior that makes cafes a place to show social class. This research was conducted through a descriptive qualitative approach using a phenomenological study type of research. The primary data sources are six people who belong to millennials who like to hang out in luxury cafes. Secondary data sources come from books, magazines, articles on the internet, and print and electronic sources. Data collection methods used were participant observation, in-depth interviews, and documentation. Data analysis was carried out by interpretive qualitative analysis through four stages, namely data collection, data reduction and presentation, and drawing conclusions. The results showed that the phenomenon of making cafes a second home was motivated by a need for a self-image of social class identity for millennials in the city of Kediri. The meanings that arise from the hangout phenomenon continuously and in the long term form perceptions as raised by people who like to show off a luxurious lifestyle on social media as a form of self-image that has a high social class. The implication of the results of this study is to form a perception of hangout culture which was initially only a physiological need then shifted to a social need, especially for millennials who follow every technological development.